2020
DOI: 10.1136/svn-2020-000476
|View full text |Cite
|
Sign up to set email alerts
|

CO2combining power and outcomes in patients with acute ischaemic stroke or transient ischaemic attack

Abstract: Background and purposeThe clinical significance of carbon dioxide combining power (CO2CP) in ischaemic cerebrovascular disease is not well established, and the role of CO2CP in the prognosis of acute ischaemic stroke (AIS) or transient ischaemic attack (TIA) has not been reported. The objective of the study was to investigate the associations between CO2CP and clinical outcomes in patients with AIS or TIA.MethodsData were derived from the China National Stroke Registry III. Patients were classified into five g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…There was a relatively lower mortality (1.1% at 3 months and 2.0% at 12 months) in our study, which was similar to the results based on the Third China National Stroke Registry (1.3% at 3 months and 2.9% at 12 months) ( 39 ). Andrade et al ( 40 ) reported a mortality of 6.9% at discharge and Paciaroni et al ( 2 ) reported a mortality of 11.5% at 3 months in stroke patients.…”
Section: Discussionsupporting
confidence: 90%
“…There was a relatively lower mortality (1.1% at 3 months and 2.0% at 12 months) in our study, which was similar to the results based on the Third China National Stroke Registry (1.3% at 3 months and 2.9% at 12 months) ( 39 ). Andrade et al ( 40 ) reported a mortality of 6.9% at discharge and Paciaroni et al ( 2 ) reported a mortality of 11.5% at 3 months in stroke patients.…”
Section: Discussionsupporting
confidence: 90%
“…Detection of trace carbon dioxide (CO 2 ) is important and can be applied to many places such as combustion products, greenhouse gas monitoring, and medical diagnosis. [1][2][3][4][5] Different concentrations of CO 2 can reflect the risk of exposing COVID-19. 6,7 Besides, a fire will cause soaring CO 2 (increasing about 25%) within four minutes.…”
Section: Introductionmentioning
confidence: 99%
“…In clinic, CO 2 combing power (CO 2 CP) as a low cost and time-saving auxiliary diagnosis usually reflects the homeostasis of acidosis and alkalosis. Accumulating evidence shows the low CO 2 CP level linking with the worse prognosis of patients with olorectal cancer, acute kidney injury, acute ischaemic stroke [17][18][19] . Similarly, the latest reports also indicates the increased lactic acid as an independent risk factor for ATAAD complications, including postoperative acute kidney and lung injury 20,21 , thereby driving the application of acid-base balance index on prognosis.…”
mentioning
confidence: 99%